2016
DOI: 10.1103/physrevlett.117.015001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale Observations of the Electron Diffusion Region of Large Guide Field Magnetic Reconnection

Abstract: We report observations from the Magnetospheric Multiscale (MMS) satellites of a large guide field magnetic reconnection event. The observations suggest that two of the four MMS spacecraft sampled the electron diffusion region, whereas the other two spacecraft detected the exhaust jet from the event. The guide magnetic field amplitude is approximately 4 times that of the reconnecting field. The event is accompanied by a significant parallel electric field (E ∥ ) that is larger than predicted by simulations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
90
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 31 publications
18
90
1
Order By: Relevance
“…Many signatures of the inner diffusion region are observed in this region, including an intense and narrow out‐of‐plane electron current, an intense broad region of electron anisotropy with T e ,∥ < T e ,⊥ followed by T e ,∥ ≫ T e ,⊥ (Figures m and l), and a moderate narrow region of electron agyrotropy, trueJ·trueE>0, all of which are discussed in the next section. As is shown in Figure c, the current near the B L reversal is largely field aligned, which is common in MMS observations of asymmetric guide field reconnection (Burch & Phan, ; Chen et al, ; Ergun et al, ; Eriksson et al, ; Genestreti et al, ). It is unlikely that MMS crossed the center of the reconnection site, or the exact X‐point, since the Hall field BM<〈〉BM,guide remained large throughout the B L reversal interval.…”
Section: Large‐scale Observations During the Magnetopause Crossingsupporting
confidence: 59%
See 1 more Smart Citation
“…Many signatures of the inner diffusion region are observed in this region, including an intense and narrow out‐of‐plane electron current, an intense broad region of electron anisotropy with T e ,∥ < T e ,⊥ followed by T e ,∥ ≫ T e ,⊥ (Figures m and l), and a moderate narrow region of electron agyrotropy, trueJ·trueE>0, all of which are discussed in the next section. As is shown in Figure c, the current near the B L reversal is largely field aligned, which is common in MMS observations of asymmetric guide field reconnection (Burch & Phan, ; Chen et al, ; Ergun et al, ; Eriksson et al, ; Genestreti et al, ). It is unlikely that MMS crossed the center of the reconnection site, or the exact X‐point, since the Hall field BM<〈〉BM,guide remained large throughout the B L reversal interval.…”
Section: Large‐scale Observations During the Magnetopause Crossingsupporting
confidence: 59%
“…Nakamura et al (), Price et al (, ), and Le et al () have all recently performed 3‐d PIC simulations of MMS EDR events. Nakamura et al () analyzed a large‐scale simulation of the very large guide field Kelvin‐Helmholtz vortex reconnection event of Eriksson et al (). Both the simulation and the data showed parallel out‐of‐plane electric fields in the trueJ·trueE>0 region that were several times larger than what is expected for the nominal fast reconnection rate of 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…The clear peaks of curl of E′ suggests that the electrons were not frozen-in to the magnetic field within this region (Goldman et al, 2016;Zhou et al, 2017). It has been reported that large guide field can magnetize electrons within the EDR (Eriksson et al, 2016;Zhou et al, 2017). It has been reported that large guide field can magnetize electrons within the EDR (Eriksson et al, 2016;Zhou et al, 2017).…”
Section: An Active X Line In the Exhaustmentioning
confidence: 89%
“…Since its launch on 12 March 2015, Magnetospheric Multiscale (MMS) has observed magnetic reconnection at the dayside MP many times (e.g., Burch et al, ; Lavraud et al, ; Zhou et al, , ). In particular, asymmetric reconnection with a large guide field has been studied by Burch and Phan () and Eriksson et al (). Since these studies focused on the physics in the vicinity of the EDR, details of the ion diffusion region (IDR) in large guide field reconnection were not investigated.…”
Section: Introductionmentioning
confidence: 99%